Characterization, in vitro cytotoxic and antibacterial exploitation of green synthesized freshwater cyanobacterial silver nanoparticles - Guna Swetha Kuraganti, Sujatha Edla, Thrimothy Dasari, Mamatha Reddy (Journal of Applied Pharmaceutical Science, 2020)
Cyanobacteria-mediated silver nanoparticles synthesis approach has proven to be more efficient and eco-friendly in achieving biomedical applications compared to physical and chemical prototypes. In the present work, the silver nanoparticles were successfully synthesized by cell-free extract of freshwater cyanobacteria, i.e., Chroococcus turgidus and Characium typicum. The cyanobacterial silver nanoparticles (CSNPs) were characterized by UV-Vis spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) analysis and were further tested for antibacterial and cytotoxic efficiency. The synthesis of CSNPs was confirmed through visible color change and shift of peaks at 430–445 nm by the UV-Vis spectroscopy. The size of CSNPs was between 22 and 34 nm and oval-shaped which were confirmed by SEM and TEM analyses. The FTIR spectra showed a new peak at the range of 3,400–3,460 cm−1 compared to control, confirming the reduction of silver nitrate. Furthermore, the antibacterial activity of CSNPs showed highest zone of inhibition with 6.9, 4.0, 2.0, and 3.0 mm against Salmonella paratyphi, Escherichia coli, Klebsiella pneumonia, and Staphylococus aureus, respectively, whereas in vitro cytotoxic activity of C. typicum and C. turgidus silver nanoparticles showed remarkable IC50 values with 43.3 and 40.9 ug/ml against MCF-7 breast cancer cell line and 20.8 and 55.7 ug/ml against HepG2 cancer cell, simultaneously.
Keywords: Freshwater cyanobacteria, silver nanoparticles, characterization, antimicrobial activity, cytotoxic activity.